Esophageal Magnetic Compression Anastomosis in Esophageal Atresia Repair: A PRISMA-Compliant Systematic Review and Comparison with a Novel Approach - Anne-Sophie Holler; Tatjana Tamara König; Caressa Chen; Michael R. Harrison; Oliver J. Muensterer (MDPI AG, 2022)
The use of magnet compression to endoscopically create an esophageal anastomosis is an intriguing approach to esophageal atresia repair, but published cases with an existing available device have demonstrated mixed success. One major shortcoming has been the formation of subsequent severe, recalcitrant strictures after primary repair. To address the limitations of the existing device, we recently introduced and reported success with specially designed bi-radial magnets that exhibit a novel geometry and unique tissue compression profile. The aim of this study is to compare the outcomes using our novel device (novel group, NG) with those of previous reports which utilized the historical device (historic group, HG) in a PRISMA-compliant systematic review. Seven studies were eligible for further analysis. Additionally, one of our previously unreported cases was included in the analysis. Esophageal pouch approximation prior to primary repair was performed more frequently in the NG than in the HG (100% NG vs. 21% HG; p = 0.003). There was no difference in the overall postoperative appearance of postoperative stricture (95% HG vs. 100% NG; p = 0.64). The number of postoperative dilatations trended lower in the NG (mean 4.25 NG vs. 9.5 HG; p = 0.051). In summary, magnetic compression anastomosis adds a new promising treatment option for patients with complex esophageal atresia. Prior approximation of pouches and a novel magnet design have the potential to lower the rate of stricture formation.